DEVELOPMENT OF PHYSICAL CHEMICAL TEACHING MATERIALS USING TASK BASED LEARNING MODEL - Sanjaya Sanjaya (Sriwijaya University Learning and Education International Conference, 2018)
Physical Chemistry Teaching Materials are generally delivered using a one-way learning model, from lecturers to students. This causes student learning activities to be low so that student learning outcomes are not optimal. To maximize learning outcomes it is necessary to improve the quality of learning, by changing learning models into task-based learning. Changing the learning model requires changing the components of teaching materials according to the learning model that has been changed. Teaching material for Physical Chemistry in Chemistry Education Program PMIPA FKIP Sriwijaya University developed contains a collection of task assignments that must be carried out by students, both individuals and groups, in such a way that the series of physical chemistry learning is in the form of a series of work assignments that follow the cycle of independent work tasks, group work and group presentations, and so on. The development of the Physics Chemistry teaching material follows the ADDIE model.